Effects of in-group bias on face recognition using minimal group procedures - Nguyen, Maia T., author; Troup, Lucy J., advisor; Draper, Bruce, committee member; Rhodes, Matthew G., committee member (Colorado State University. Libraries, 2014)
The current series of experiments examined the effects of social categorization on face recognition. The use of minimal group procedures was expected to enhance recognition for in-group members compared to out-group members. In Experiment 1, participants were assigned to 1 of 3 conditions: name study--participants studied a list of 16 names associated with their in-group [red or green], numerical estimation--participants were randomly divided into 2 groups [red or green] after estimating the number of dots in a series of 10 images, and the control condition. This was followed by a study phase in which participants were presented with a total of 32 female and male Caucasian faces on red or green backgrounds. A final recognition test was given following a filler task. Experiment 2 had two of the previously used conditions, name study and control. Faces were presented on red and green backgrounds during test--with old faces presented on the same background as seen at study. Experiment 3 presented a subset of stimuli used in Experiment 2 with a longer presentation time (10 seconds). Findings suggest only moderate difference in response bias between experimental and control groups overall in Experiments 2 and 3. Moderate differences in hits, false alarms, and d' were also found in Experiment 3 between experimental conditions. Group membership did not elicit significant effects on measures of accuracy, reaction time, and confidence ratings.
Keywords: face recognition; minimal groups